Comparison of Roles between Alcohol Ablation and Surgical Myectomy in Hypertrophic Cardiomyopathy - Nico Kusuma; Raymond Pranata; Rachel Vania; Bambang Budi Siswanto (Jurnal Kardiologi Indonesia, 2017)
Hypertrophic cardiomyopathy is a genetic myocardial disease that may extend to leftventricular outflow tract obstruction. Alcohol septal ablation (ASA) is preferred for itsnon-surgical, agreed as the safest way for advanced aged, or those with high risk for surgicalprocedure or comorbidities. On the other hand, surgical myectomy (SM) remainsas gold standard, established to be the most consistent to achieve optimal hemodynamicand spare longevity, regardless selective use. This article reviews the advantages anddisadvantages between SM and ASA ablation from its outcome, mortality, pre- and postprocedural,and patient’s profile selection.